2019
DOI: 10.1021/acsnano.8b07902
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Antibacterial Activity of Nanoparticles Made of β-Cyclodextrins Potentiates Their Effect as Drug Nanocarriers against Tuberculosis

Abstract: Multi-drug-resistant tuberculosis (TB) is a major public health problem, concerning about half a million cases each year. Patients hardly adhere to the current strict treatment consisting of more than 10 000 tablets over a 2-year period. There is a clear need for efficient and better formulated medications. We have previously shown that nanoparticles made of cross-linked poly-β-cyclodextrins (pβCD) are efficient vehicles for pulmonary delivery of powerful combinations of anti-TB drugs. Here, we report that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…pβCD can prevent the colonization of macrophages by Mtb and does not produce toxicity in the body. In addition, pβCD can also induce macrophage apoptosis and promote the exhaustion of infected cells [157].…”
Section: Pulmonary Tuberculosismentioning
confidence: 99%
“…pβCD can prevent the colonization of macrophages by Mtb and does not produce toxicity in the body. In addition, pβCD can also induce macrophage apoptosis and promote the exhaustion of infected cells [157].…”
Section: Pulmonary Tuberculosismentioning
confidence: 99%
“…123 Some recent case studies of the CDs in the optimal drug delivery of drugs, proteins, peptides and aptamers are reported in the Table 3. [124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140] CDs can be moulded into various types of formulation for proving ease the drug delivery by diverse routes of administration.…”
Section: An Account Of Recent Advances In Cds For Optimal Drug Deliverymentioning
confidence: 99%
“…This result demonstrated the benefit of using the pulmonary route of infection to target more specifically Mtb within reservoir cells. Using the same experimental design, we recently showed that ETH itself is ineffective when given intranasally in lungs during two weeks, 34 therefore a 6-fold reduction of the bacterial burden obtained after only 6 administrations of ETH-B NPs is encouraging. The next studies will aim at investigating whether an increase in the treatment duration or in the amount of administrated drugs could improve ETH-B efficacy.…”
Section: In Vivo Evaluation In a Model Of Mtb Infected Micementioning
confidence: 91%